2022
DOI: 10.2147/idr.s354660
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of a Loop-Mediated Isothermal Amplification Assay for the Diagnosis of Pulmonary Tuberculosis in Children Using Bronchoalveolar Lavage Fluid

Abstract: Objective Using TB-LAMP for diagnosing pediatric PTB, however, still requires systematic evaluation. Here, we evaluated TB-LAMP performance alone and in combination with conventional assays for diagnosing PTB in Chinese children, using mycobacterial culture or CCRS (the composite clinical reference standard) as references. Design or Methods BALF samples were collected at Shenyang Tenth People’s Hospital from 251 children susceptible to TB infection with indications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…BALF is the most common used respiratory sample type for the diagnosis of PTB besides sputum, which is also preferred by clinicians due to its closer proximity to the lesion. Multiple studies have reported the capability of different molecular tests to diagnose PTB in BALFs, such as Xpert MTB/RIF assay, SAT-TB, LAMP, next-generation metagenome sequencing, nanopore sequencing, etc., with sensitivities raging from 45.18-94.4% [21][22][23][24][25][26] . The comparatively lower results of the Xpert MTB/RIF assay in our study than those previously studies may be related to several factors, including study site, sample source, and the operator, suggesting that we need to improve the level of testing within our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…BALF is the most common used respiratory sample type for the diagnosis of PTB besides sputum, which is also preferred by clinicians due to its closer proximity to the lesion. Multiple studies have reported the capability of different molecular tests to diagnose PTB in BALFs, such as Xpert MTB/RIF assay, SAT-TB, LAMP, next-generation metagenome sequencing, nanopore sequencing, etc., with sensitivities raging from 45.18-94.4% [21][22][23][24][25][26] . The comparatively lower results of the Xpert MTB/RIF assay in our study than those previously studies may be related to several factors, including study site, sample source, and the operator, suggesting that we need to improve the level of testing within our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, propofol is renowned for its rapid onset and short duration of action. It facilitates swift induction and recovery from anesthesia, making it suitable for procedures requiring promptcompletion [11][12][13] . Yet, propofol can induce significant cardiovascular and respiratory depression, especially in pediatric patients 14 .…”
mentioning
confidence: 99%